Management Planning and Its Development To Improve The Performance of Company Employees - Ahmad Zaelani Adnan; Endrixs Endrianto; Ninin Asmiah; Aisyandani Muqsitha (Return : Study of Management, Economic and Bussines, 2022)
Background: Management planning in improving employee performance in a company, namely providing training, applying discipline and providing motivation at work Aim: This study aims to find out how management planning in improving employee performance in a company. Method: This research is qualitative research, so the data analysis applied is qualitative. Data collection is the activity of deciphering or collecting all data that has been obtained from the field in the form of observations, interviews and data in the form of certain documents without exception Data presentation, efforts to present data to see the overall picture or certain parts of this research, Data reduction is the process of selecting the focus of attention on simplifying, abstracting, and transforming emerging data and written records in the field Conclusion and verification, that is, an attempt to achieve meaning to the collected data, by looking for patterns, relationships of equations of things that often arise Findings: The implementation of management in improving employee performance in a company is conducting training, applying time in work and providing motivation in the form of rewards and punishments. Evaluation of management planning in improving employee performance runs effectively and efficiently, if this is associated with syarah management then this is in accordance with the three principles of sharia management, namely fairness, trust and accountability as well as communicative.